The Influence of supply chain management strategies on supply chain performance within the food and beverage industry in Kenya - Mwaura, Joan Wanjiru (Strathmore University, 2021)
This study aimed to see how supply chain management affected supply chain success in Kenya's food and beverage industry. The importance of the food and beverage industry in Kenya's economic development cannot be overstated. The market, however, is underperforming due to the fierce competition it faces from the importation of food and drinks from other countries. Previous analysis has also shown that the food and beverage industry has a long way to go before realizing the full benefits of a fully connected supply chain management scheme. Since this aspect has not been thoroughly studied, most distribution departments, for example, do not grasp precisely how supply chain management provides value for their clients. Previous studies have been conducted in various geographical areas. They have used several factors, scopes, and methodologies, resulting in a wide range of findings that, to the best of the researcher's understanding; do not contribute to analyzing supply chain management's effect on supply chain success in Kenya, necessitating the need for this analysis. The food and beverage sector was used as the target demographic in this analysis, and it was analyzed using a quantitative method. Besides, the researcher used questionnaires to gather accurate information about the company's behaviors, beliefs, and perceptions. The research used linear regression and correlation statistics to analyze the relationship between supply chain management and supply chain efficiency. The findings indicate that organizations in the food and beverage industry strive to achieve high supply chain performance levels. As was revealed by their coefficients’ magnitudes, Supply chain agility at .611 had the most negligible impact on supply chain performance. Supply chain integration at .813 had the highest impact on supply chain performance and was closely followed by supply chain collaboration at .779. The research concluded that for organizations to achieve sufficient supply chain performance levels they had to employ all the three variables analyzed in unison as initiating one and living out the others was found to have minimal impact.
A research project submitted in partial fulfillment of the requirements for the Degree of Bachelor of Commerce